EFFECTIVENESS OF FORMULA BASED ON CASEIN HYDROLYSATE IN CHILDREN WITH ALLERGY TO PROTEINS OF COW'S MILK - I.V. Makarova; V.S. Tikhonova; O.V. Zhiglinskaya; E.A. Medvedeva; R.N. Arakelyan; E.Yu. Vovk ("Paediatrician" Publishers LLC, 2010)
Dietotherapy along with medicinal and external treatment is one of components of complex treatment of atopic dermatitis (AD) in children. Severe forms of alimentary allergy are treated with special formulas based on casein hydrolisates. Clinical effectiveness of such formula was studied in 20 patients 2-7 months old intolerant to proteins of cow's and goat's milk. Treatment resulted in remission achievement, lessening of external therapy and cancellation of medicinal one in all children including those with cutaneous and gastrointestinal symptoms of AD. Key words: children, atopic dermatitis, dietotherapy, casein hydrolysate, SCORAD. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):97-101)